Stress hormones and post-traumatic stress disorder in civilian trauma victims: a longitudinal study. Part I: HPA axis responses - Shalev, Arieh Y.; Videlock, Elizabeth J.; Peleg, Tamar; Segman, Ronen; Pitman, Roger K.; Yehuda, Rachel (The international journal of neuropsychopharmacology, 2008)
The aim of the study was to evaluate the association between post-traumatic disorder (PTSD) and hypothalamic–pituitary–adrenal (HPA) axis responses to the triggering trauma. A companion paper evaluates the adrenergic response and interactions between the two. We measured plasma and saliva cortisol, hourly urinary excretion of cortisol, plasma levels of adrenocorticotropin (ACTH), and the leukocyte glucocorticoid receptor (GR) density of 155 non-injured survivors of traumatic events (91 males and 64 females; 125 road traffic accidents, 19 terrorist attacks, 11 others). Measurements were taken during survivors' admissions to an emergency room (ER) of a general hospital, and in the mornings, 10 d, 1 month, and 5 months later. Symptoms of peri-traumatic dissociation, PTSD, and depression were assessed on each follow-up session. The clinician-administered PTSD scale (CAPS) conferred a diagnosis of PTSD at 5 months. Survivors with (n=31) and without (n=124) PTSD at 5 months had similar levels of hormones at all times. Plasma cortisol levels decreased with time in both groups. Female subjects had lower ACTH levels than males. PTSD in females was associated with higher levels of ACTH. In unselected cohorts of trauma survivors, PTSD is not preceded by a detectable abnormality of peripheral HPA axis hormones.